2004
DOI: 10.1111/j.1471-0528.2004.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Home‐based versus hospital‐based postnatal care: a randomised trial

Abstract: Objective To compare a shortened hospital stay with midwife visits at home to usual hospital care after delivery. Design Randomised controlled trial.Setting Maternity unit of a Swiss teaching hospital.Population Four hundred and fifty-nine women with a single uncomplicated pregnancy at low risk of caesarean section. Methods Women were randomised to either home-based (n ¼ 228) or hospital-based postnatal care (n ¼ 231).Home-based postnatal care consisted of early discharge from hospital (24 to 48 hours after de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 22 publications
2
71
1
8
Order By: Relevance
“…Of the women with problems, 42% attended health services seeking help. However, regarding hospital readmission, there was no difference between those discharged earlier or later (1,4) . Additionally, women who were discharged within 48hrs after delivery were significantly more likely to be depressed at 5-6 months postpartum (14) .…”
Section: The Effects Of Ed On New Mothersmentioning
confidence: 79%
See 3 more Smart Citations
“…Of the women with problems, 42% attended health services seeking help. However, regarding hospital readmission, there was no difference between those discharged earlier or later (1,4) . Additionally, women who were discharged within 48hrs after delivery were significantly more likely to be depressed at 5-6 months postpartum (14) .…”
Section: The Effects Of Ed On New Mothersmentioning
confidence: 79%
“…Although there is no conclusive evidence that proves infants discharged early have an increased risk of morbidity (1) , in 2000 a medical records analysis suggested that children who were discharged on the day of birth are more likely to be re-hospitalized with jaundice (p=0.01), however no difference was described in the prevalence of jaundice; also dehydration was higher in ED newborns (p=0.01) compared with those who were discharged later (12) . Furthermore, one study (4) noted that infants who were discharged early were more likely to be readmitted during the first six months postnatal compared with newborns discharged later (p= 0,004), nevertheless, the rate of neonate rehospitalization during the first month postpartum was not significantly different among the groups. A retrospective study, which included the medical records of American infants (13) , found a significant positive association between a postpartum discharge within 24hrs and newborn mortality at 28 days of birth (OR 3.65, 95% CI 1.56, 8.54).…”
Section: The Effects Of Ed On Infantsmentioning
confidence: 96%
See 2 more Smart Citations
“…The most popular medically-based interventions are antidepressant medication (Marcus et al, 2001), estrogen therapy (Cattel & King, 1996;Gregoire, et al, 1996;Grigoriadis & Kennedy, 2002), home health care (Appleby et al, 2003;Armstrong et al, 1999;Mauthner, 1997;Parke & Hardy, 1997, Simons et al, 2003, inpatient hospitalization (Boulvain et al, 2004), psychiatric day treatment programs (Boath et al, 1999) and educational materials provided at discharge from maternity floors (Ahn & Kim, 2004;Garg et al, 2005).…”
Section: Ppd Treatmentsmentioning
confidence: 99%